37.1k views
3 votes
Simplify: -4 1/5 (-13 1/10) (5 points)

(A) 8 9/10

(B) -8 9/10

(C) -17 3/10

(D) 17 3/10

2 Answers

4 votes

Answer:

(C) -17 3/10

Explanation:

We assume you want the sum

... (-4 1/5) + (-13 1/10)

... = -4 -1/5 -13 -1/10

... = (-4 -13) +(-2/10 -1/10) . . . . . . rewrite 1/5 as 2/10

... = -17 -3/10------------

... = -(17 3/10)-----------

User Jeppe Liisberg
by
5.9k points
4 votes

Answer:

(C) -17 3/10

Explanation:

We assume you want the sum ...

... (-4 1/5) + (-13 1/10)

... = -4 -1/5 -13 -1/10

... = (-4 -13) +(-2/10 -1/10) . . . . . . rewrite 1/5 as 2/10

... = -17 -3/10

... = -(17 3/10)

User Kitesurfer
by
6.4k points